К вопросу о роли познавательных деятельности студентов ВУЗА в самостоятельной работе - Иванова, Е.Н.; Старжинская, Ю.С. (My University, 2016)
This article discusses some of the features of independent work of students of the university. Attention is paid to the development of the student's ability to analyze the basic theoretical concepts for active use in training activities.
Keywords: cognitive activity; independence; independent work; hard work; motivation